Task-based learning activities to enhance speaking skills among students in third year of bachillerato "a” afternoon session at unidad educativa del milenio bernardo valdivieso of the city of loja, 2018−2019 academic year. - Poma Tacuri, Manuel Alejandro (2019)
The objective of this research was to enhance speaking skills among students in third year of bachillerato “A” afternoon session at Unidad Educativa del Milenio Bernardo Valdivieso of the city of Loja, 2018-2019 school year. The methods used were: the scientific method, the descriptive method, the statistical method, and the analytic-synthetic method which were useful to provide of main information, explain and describe the phases of the study, tabulate and present it in tables, and to draw conclusions and recommendations. The instruments used to collect data were a pre and post-test and, pre and post-questionnaire applied to 36 students. Moreover, observation sheets and field notes were useful to record students’ progress. The results gathered demonstrated that students speaking skills enhancement was slight. In conclusion, Task-Based Learning activities helped students to feel more confident, collaborate and interact with one another and, structuring spoken language appropriately